Igazságosság, természetjog, új emancipáció : A zsidó kisebbségi jogok Junger József (1911–1945) értelmezésében - Schweitzer, Gábor (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2025)
The draft of Act IV of 1939 on the public and economic restrictions of Jews declared Jews in Hungary an ethnic group for the purpose of public legal segregation. This provision was eventually removed from the text of the law. In the period of anti-Semitic legislation that dismantled the achievements of denominational emancipation of the liberal era, one of the efforts of Jewish communities was to develop survival strategies. The theorists of the Zionist movement, who were inherently critical of the processes of liberal emancipation and assimilation, proclaimed the necessity of a new emancipation based on an ethnic minority status in the shadow of the draft of Act IV. of 1939. The articles of József Junger, lawyer and vice-president of the Hungarian Zionist Federation, published in this period were primarily aimed at the legal and theoretical foundation of this new emancipation based on the ethnic minority status. József Junger believed that a new emancipation of Jews based on ethnic ground could be legitimized on the basis of the principles of justice and natural law.